2021
DOI: 10.1063/5.0066346
|View full text |Cite
|
Sign up to set email alerts
|

Vertical field inhomogeneity associated with threading dislocations in GaN high electron mobility transistor epitaxial stacks

Abstract: A measurement technique combining Kelvin-Probe Force Microscopy (KPFM) with substrate bias is developed and demonstrated on AlGaN/GaN-on-Si device structures, under conditions relevant to the effect of off-state drain bias stress in transistors. For high substrate bias, the measurements show a significantly lowered surface potential surrounding a small proportion of the dislocations imaged with atomic force microscopy (AFM), laterally extending on a scale of up to a micrometer. Both the density and the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[13][14][15][16][17][18] Currently, GaN-on-Si wafers are commercially available up to 8″ diameter and close to a cost target of 1.5 $/cm 2 for epitaxial material, where GaN will be cost-competitive with Si-based components at the device-level. 3,4 Currently, GaN-on-Si structures have epilayer thickness of 4-6 μm, producing a voltage handling capability of 650 V. In such GaN-on-Si structures, it has recently been reported that there are vertical field inhomogeneities associated with threading dislocations, which produce charge carrier trapping and increased leakage currents [19][20][21][22][23][24][25][26][27][28][29][30] and many studies have correlated dislocations with changes in local materials properties. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Dislocation densities for AlGaN/GaN-on Si are currently ∼10 9 cm 2 and the screw and mixed type dislocations create leakage paths in Schottky diodes under high voltage reverse biases.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18] Currently, GaN-on-Si wafers are commercially available up to 8″ diameter and close to a cost target of 1.5 $/cm 2 for epitaxial material, where GaN will be cost-competitive with Si-based components at the device-level. 3,4 Currently, GaN-on-Si structures have epilayer thickness of 4-6 μm, producing a voltage handling capability of 650 V. In such GaN-on-Si structures, it has recently been reported that there are vertical field inhomogeneities associated with threading dislocations, which produce charge carrier trapping and increased leakage currents [19][20][21][22][23][24][25][26][27][28][29][30] and many studies have correlated dislocations with changes in local materials properties. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Dislocation densities for AlGaN/GaN-on Si are currently ∼10 9 cm 2 and the screw and mixed type dislocations create leakage paths in Schottky diodes under high voltage reverse biases.…”
mentioning
confidence: 99%
“…As per [6], based on the information on the presence of inhomogeneity of the vertical electric field across the barrier of III-nitrides [6,9,22,23], the current due to the FN tunneling mechanism is position-dependent. Therefore, the FN-related current which leaks through a part of the barrier that boasts a higher electric field dominates the total leakage current through the barrier.…”
mentioning
confidence: 99%